Sorting, incentives and risk preferences: evidence from a field experiment - Charles Bellemare; Bruce S. Shearer (Institute for the Study of Labor (IZA), 2006)
The, often observed, positive correlation between incentive intensity and risk has been explained in two ways: the presence of transaction costs as determinants of contracts and the sorting of risk-tolerant individuals into firms using high-intensity incentive contracts. The empirical importance of sorting is perhaps best evaluated by directly measuring the risk tolerance of workers who have selected into incentive contracts under risky environments. We use experiments, conducted within a real firm, to measure the risk preferences of a sample of workers who are paid incentive contracts and face substantial daily income risk. Our experimental results indicate the presence of sorting; Workers in our sample are risk-tolerant. Moreover, their level of tolerance is considerably higher than levels observed for samples of individuals representing broader populations. Interestingly, the high level of risk tolerance suggests that both sorting and transaction costs are important determinants of contract choices when workers have heterogeneous preferences.
Keywords: J33; M52; C93; 330; risk aversion; sorting; incentive contracts; field experiments